PHYTO-ASSESSMENT OF SOIL HEAVY METAL ACCUMULATION IN TROPICAL GRASSES - C. C. Ng; S. H. Law; N. B.Amru; M. R. Motior; B. A. Mhd Radzi (Journal of Animal and Plant Sciences, 2016)
Tropical grasses are fast growing and often used for phytoremediation. Three different types of tropical grasses: Vetiver (V. zizanoides), Imperata (I. cylindrical) and Pennisetum (P. purpureum) tested in different growth media of spiked heavy metal contents under the glasshouse environment of RimbaIlmu for 60-day. The growth performance, metals tolerance and phyto-assessment of cadmium (Cd), lead (Pb), zinc (Zn) and copper (Cu) in shoots and roots were assessed using flame atomic absorption spectrometry (FAAS).Tolerance index (TI), translocation factor (TF), biological accumulation coefficient (BAC), biological concentration factor (BCF), and uptake efficacy was applied to evaluate the metal translocation ability among all three grasses. All three grasses showed significantly higher (p<0.05) accumulation of the total heavy metals in the spiked metal treatment compared with other tested treatments. Vetiver accumulated remarkably higher total concentration of Cd (93.08 ± 3.81 mg/kg) and Zn (1284.00 ± 234.83 mg/kg) than both Imperata and Pennisetum. The overall trend of heavy metals accumulation for all three grasses followed the order of Zn >Pb> Cd >Cu. The results of study suggested that both Imperata and Pennisetum are commendable and potential phytoextractors for Zn as well as phytostabilizers for Cd, Pb and Cu, respectively.
Keywords: Vetiver; Imperata; Pennisetum; Spiked heavy metal; Heavy metal accumulation